A Narrative Engagement Framework to Understand HPV Vaccination Among Latina and Vietnamese Women in a Planned Parenthood Setting. (October 2017) - Hopfer, Suellen; Garcia, Samantha; Duong, Huong T.; Russo, Jennefer A.; Tanjasiri, Sora P.
Disparities in cervical cancer and human papillomavirus (HPV) vaccination persist among Vietnamese and Latina women. Through a partnership with Planned Parenthood of Orange and San Bernardino Counties (PPOSBC) in Southern California, we conducted in-depth interviews with young adult Latina ( n = 24) and Vietnamese ( n = 24) women, and PPOSBC staff ( n = 2). We purposively sampled vaccinated women to elicit HPV vaccine decision narratives to uncover rich data on motivators, cultural values, and implicit vaccine attitudes. Unvaccinated women were interviewed to identify barriers. Women were also asked to discuss their observations of men's HPV vaccine attitudes. Narrative engagement theory guided the study privileging the meaning women ascribed to their experiences and conversations related to vaccine decision making. Vaccine decision narratives included (a) mother–daughter narratives, (b) practitioner recommendation of HPV vaccination, (c) independence narratives among Vietnamese women, (d) HPV (un)awareness narratives, and (d) school exposure to HPV knowledge. Barriers to vaccinating included trust in partner HPV status, and family silence and stigma about sexual health. Participants conveyed the importance of including messages aimed at reaching men. Practitioners described insurance barriers to offering same day vaccination at PPOSBC health center visits. Narrative communication theory and methodology address health equity by privileging how Vietnamese and Latina women ascribe meaning to their lived experiences and conversations about HPV vaccination. Identifying authentic and relatable vaccine decision narratives will be necessary to effectively engage Vietnamese and Latina women. These findings will guide the process of adapting an existing National Cancer Institute research-tested HPV vaccine intervention.